The Effect of Servant Leadership on Job Outcomes: The Mediating Role of Trust in Coworkers - Rashid, Adnan Mahmod M.; Ilkhanizadeh, Shiva (Frontiers in Communication, 2022)
A good deal of evidence indicates that servant leadership play a critical role in employees' job outcomes. However, research studies on the variables that could mediate the effect of servant leadership in determining this relationship are relatively few. This study contributed in the deeper understanding of Servant Leadership culture in the workplace that promotes a culture that promotes trust and positive job outcomes among employees in banking organisations. While contributing to this body of work, this research utilized the framework of leader-member exchange and social exchange theories. This study also examines the mediating effect of "trust in coworkers" in the effect of "servant leadership" on employee job outcomes. Survey data were sourced from 315 bank employees and managers in Northern Cyprus. Partial least square structural equation modelling was utilized with the aid of WarpPLS (7.0) to test the study hypotheses. Servant leadership was found to have a direct and indirect relationship with employees' career satisfaction, service recovery performance, and innovative work behaviour. In contrast, the servant leadership relationship with job satisfaction was indirect. In addition, trust in coworkers was found to be a mediator in the relationship between servant leadership and employees' job outcomes. The theoretical and practical implications of this study were highlighted.